The Changing Landscape of Anticoagulation in Pediatric Extracorporeal Membrane Oxygenation: Use of the Direct Thrombin Inhibitors - Neunert, Cindy; Chitlur, Meera; van Ommen, Cornelia Heleen (Frontiers in Medicine, 2022)
Bleeding and thrombosis frequently occur in pediatric patients with extracorporeal membrane oxygenation (ECMO) therapy. Until now, most patients are anticoagulated with unfractionated heparin (UFH). However, heparin has many disadvantages, such as binding to other plasma proteins and endothelial cells in addition to antithrombin, causing an unpredictable response, challenging monitoring, development of heparin resistance, and risk of heparin-induced thrombocytopenia (HIT). Direct thrombin inhibitors (DTIs), such as bivalirudin and argatroban, might be a good alternative. This review will discuss the use of both UFH and DTIs in pediatric patients with ECMO therapy.